Effect of 650 nm laser photobiomodulation therapy on the HT-7 (shenmen) acupoint in the Mus musculus model of Parkinson's disease - Suhariningsih Suhariningsih; Suryani Dyah Astuti; Herdiani Nur Kusumawati; Amalia Fitriana Mahmud; Maya Septriana; Lale Rozykulyyeva; Yunus Susilo; Ardiansyah Syahrom (Heliyon, 2023)
Background: Parkinson's disease is one of the neurodegenerative conditions that impacts 1–2% of the world's population. The only effective therapy for this condition today is to restore the biochemical function of the diseased dopamine neurons by giving them Levodopa or L-3,4-dihydroxyphenylalanine (l-DOPA). The risk of progenitor stem cells, though, is the growth of teratomas or the uncontrolled growth of cells. As a result, an alternative or additional method is needed, such as photobiomodulation therapy using a laser diode. In this research, male mice (Mus musculus), which were used as models for Parkinson's disease in an in vivo paraquat study, to determine the optimal dose of photobiomodulation therapy and a laser diode was used as a treatment. Methods: The three sample groups are Group P-L- (control group, induced by 0.9% NaCl), Group P + L- (only caused by paraquat), and Group P + L+. (Treatment group, treated by paraquat and photobiomodulation therapy with a laser diode). Photobiomodulation treatment doses of 0.14 J, 0.29 J, 0.37 J, 0.76 J, 1.14 J, and 1.52 J were used in the P+L+ subgroups (6 groups). The laser diode generated a continuous wave with a wavelength of 658 nm, a beam spot of 2.10 mm, and an output power of 15.42 mW. After treatment, the histopathology results of each sample were inspected under a microscope. Result: In Parkinson's disease-affected mice, paraquat has been shown to reduce the number of neurons. According to the results of the histopathological examination, photobiomodulation therapy using a laser diode (P + L+) on the HT-7 (Shenmen) may raise the quantity of neurons and the proportion of healthy cells in the mouse brain. Conclusion: The effective radiated energy of the photobiomodulation therapy using laser diode treatment on the muscle musculus cell model of Parkinson's disease is 0.76 J.